The Representation of Movement in the Drawing of Children with Physical Disabilities (Al-Academy, 2025)
Objectives: this study investigates the impact of physical disabilities on children's visual representation of movement and highlights the role of gender in this context.Methodology: descriptive-analytical approach and Descriptive-comparative was used to examine the drawings of the study sample.Results: The results showed a clear representation of movement, particularly in the limbs and joints, in the drawings of children with normal development, compared to the drawings of children with physical disabilities,  and normal females excelled in representing the movement in all research samples.. And the study concludes that representing movement requires cognitive interpretation, which may be limited in children with physical disabilities unless they are exposed to artistic training.